2017
DOI: 10.1101/161679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental constraints on genome evolution in four bilaterian model species

Abstract: Developmental constraints on genome evolution have been suggested to follow either an early conservation model or an "hourglass" model. Both models agree that late development strongly diverges between species, but debate on which developmental period is the most conserved. Here, based on a modified "Transcriptome Age Index" approach, i.e. weighting parameters by expression level, we analyzed the constraints acting on three evolutionary traits of protein coding genes (strength of purifying selection on protein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Third, rates of coding sequence evolution (dN/dS or KA/KS) for genes expressed differentially across development provide a means of assessing selection on the encoded protein sequences used in genetic networks. A simple way of testing for trends in purifying selection and positive selection across ontogeny is to compare the average dN/dS value for the set of genes with peak expression at a given developmental timepoint Ward 2005, Davis et al 2005) or an expression-weighted mean dN/dS value for all genes expressed at a given timepoint (Quint et al 2012, Liu andRobinson-Rechavi 2018b). When a multi-species phylogeny is used, or if polymorphism data are incorporated in a McDonald-Kreitman testing framework, then positive selection may be distinguished from relaxed purifying selection (Liu and Robinson-Rechavi 2018a).…”
Section: Concentricmentioning
confidence: 99%
“…Third, rates of coding sequence evolution (dN/dS or KA/KS) for genes expressed differentially across development provide a means of assessing selection on the encoded protein sequences used in genetic networks. A simple way of testing for trends in purifying selection and positive selection across ontogeny is to compare the average dN/dS value for the set of genes with peak expression at a given developmental timepoint Ward 2005, Davis et al 2005) or an expression-weighted mean dN/dS value for all genes expressed at a given timepoint (Quint et al 2012, Liu andRobinson-Rechavi 2018b). When a multi-species phylogeny is used, or if polymorphism data are incorporated in a McDonald-Kreitman testing framework, then positive selection may be distinguished from relaxed purifying selection (Liu and Robinson-Rechavi 2018a).…”
Section: Concentricmentioning
confidence: 99%
“…This provides a regulatory basis for the hourglass expression pattern. It was suggested that pleiotropic constraints might play important roles in the conservation of phylotypic stage (Duboule 1994; Raff 1996; Hu et al 2017; Liu and Robinson-Rechavi 2018a). Since we found the highest conservation at the phylotypic stage for both stage specific enhancers and all enhancers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the two evolutionary mechanisms (purifying versus positive selection) may not be mutually exclusive. In terms of protein sequence, for example, the lower sequence evolution in the phylotypic period appears to be caused by both strong purifying selection and weak positive selection (Liu and Robinson-Rechavi 2018a;Liu and Robinson-Rechavi 2018b;Coronado-Zamora et al 2019). To investigate the underlying regulatory mechanisms, and the contribution of positive selection at regulatory elements, to the hourglass model, we performed DNase-seq to identify active regulatory elements across multiple matched embryonic development stages in two distant Drosophila species: D. melanogaster and D. virilis.…”
Section: Introductionmentioning
confidence: 99%
“…Median gene expression (CPM) values were calculated for each developmental stage and sex. These values were used to calculate Tau, an index of specificity of gene expression during development (Yanai et al 2004;Liu and Robinson-Rechavi 2018) Values of Tau range from zero (broadly expressed during development) to one (gene expressed in only one stage). Tau is generally used to quantify the tissue-specificity of gene expression (Yanai et al 2004).…”
Section: Stage Specific Gene Expressionmentioning
confidence: 99%